Study of Groundwater Table Variations and Drought Monitoring Using GRI Index in Shiraz Plain (Maharloo-Bakhtegan Watershed) - I. Saleh; S. Zandifar; M. Khazaei (علوم آب و خاک, 2025)
Groundwater resources are affected by long-term drought conditions and have received less attention than other issues. The current research was carried out to investigate and zone the quantitative fluctuations of groundwater as well as the temporal analysis of groundwater drought using GRI in the study area of Shiraz in the Maharloo-Bakhtegan watershed. The zoning of groundwater table variations was done in the ArcGIS environment, and a representative hydrograph of the aquifer was prepared using 15-year data (2003-2018) of groundwater resources divided into three five-year periods. Also, the drought of the groundwater resources of the studied plain was investigated using the GRI index. According to the results, the highest level of the groundwater table is related to the northwestern area of the plain by 1810.1 m in October 2007, and the lowest water table was observed in the southern study area with the amount of 1423.6 m in October 2017. Also, the results showed that the groundwater table faced a drop of 6 m and an average annual drop of 0.5 m during the studied 15 years. The volume changes of the reservoir also indicated that, in addition to consuming the entire renewable reserve, a large part of the fixed reserve has also been exploited in the past years. The descending trend of GRI and its intensification in the last years of the studied period is one of the most important results of this research, which occurred due to population growth and increasing cultivated area, a decrease in precipitation, and climate change.